EFFECT OF THE APPLICATION OF GOAT DUNG ON THE BIOREMEDIATION OF POLLUTED SOIL BY HYDROCARBON DEGRADING BACTERIA: A MICROCOSM STUDY (FUDMA JOURNAL OF SCIENCES, 2021)
Biostimulation is an effective means of enhancing bioremediation of toxic compounds. In this study, goat dung was used as an additional source of nutrients to improve the degradation of petroleum hydrocarbons in a heavily contaminated soil. Soil samples collected from a mechanic workshop in Zaria, Nigeria, was subjected to microcosm studies in a screen house and three proportions (2%w/w, 3%w/w, 4%w/w kg-1.soil) of goat dung added to the soil samples. The effect of the addition of nutrients from the goat dung on the hydrocarbon degrading bacterial community in the soil was determined by measuring the hydrocarbon utilizing bacterial counts, percentage degradation of hydrocarbon and biostimulation efficiency. At the end of the seven-week experiment, it was observed that 4% w/w of goat dung had the highest hydrocarbon utilizing bacterial count but, the maximum percentage hydrocarbon degradation occurred in the treatment with 2% w/w goat dung and biostimulation efficiency was optimum with both 2% w/w and 4% w/w goat dung. Nutrient addition can be an effective tool during bioremediation, however, laboratory scale studies should be conducted prior to field studies in order to achieve maximum results
Keywords: bacteria, biostimulation, hydrocarbon, soil, goat dung